Severe anemia of uncertain origin in a patient with advanced gastric cancer - N. V. Zhukov (Онкогематология, 2022)
Case report of severe anemia of unknown origin and delayed intravascular hemolysis of transfused blood products in 27 years old female patient with stage IV gastric adenocarcinoma. Article presented diagnostic process with mistakes analysis and literature review.